Sistema de comunicación visual para unidades educativas de la ciudad de Tulcán - Montenegro Ortega, Jhony Fernando (2016)
The present investigation consists of three chapters that are explained summarizing its development in each chapter. At the present time the visual communication is vital in the companies and 1 not eat in the educational institutions, through the technology the communication has gone evolving the forms of the communication. The educational units of the city of Tulcán have a great flow of people for what is vital the señalética to offer the necessary information. The present project of creating a syslem señalética for the educational units of Tulcán is bom of the necessity to offer an internal better visual aspect and the communication. In the first chapter the origin of the visual communication is explained and how it influences in offering orientation through colors, typography and pictograms, graphics 0r íconos. Also the evolution of the signaling until arriving to the señalética where they influence several aspects like the environmental topic, personality and to thal users are directed. The theoretical bases on the visual communication and the señalética help to solve the problem on the escases of the señalética. In the second chapter it is talked about the sector where he/she is carried out the investigation and the application of the methodology and technical as the survey that he'she helps obtain information through the analysis of the answers of those interviewed. Of equal it forms with the analysis of experts the viability of the project it is determined since in none of the institutions it doesn't have a system complete señalético. The last chapter tries on the development of the proposal where he/she takes the process to carry out the different steps of the system señalético of the educational units but that it will be applied in the Educational Unit Isaac Acosta, the graphic system is elaborated with the information obtained as the colors of the institution, the areas, the services and the whole necessities that ¡t requires, you norm the locations of the señalética through a manual señalético that will allow to future to maintain the internal image in case that is implemented new records señaléticas.